Differentiating Indexation in Dutch Pension Funds - Roel Beetsma; Alessandro Bucciol (Tinbergen Institute, 2010)
We investigate numerically how indexation of funded pensions for inflation can be differ-entiated across the various groups of fund participants. The pension arrangement is modelledafter the Dutch situation. While the aggregate welfare consequences are small, group-specific consequences are more substantial with the workers and future born losing and retirees bene-fitting from a shift away from uniform indexation. Those welfare shifts result from systematicredistribution of welfare rather than shifts in the benefit of risk sharing provided by the system.
Keywords: H55; I38; C61; 330; indexation; funded pensions; welfare effects; pension buffers; stochastic simulations; Pensionskasse; Inflation; Umlageverfahren; Rentenreform; Gesetzliche Rentenversicherung; Wohlfahrtsanalyse; Niederlande